Serviço Social e o uso de drogas: um estudo sobre a reinserção social de pessoas em situação de dependência de álcool e outras drogas - Silva, Denis Barreto da (2015)
This work aimed to investigate the intervention of Social Work in process of social reintegration of persons in situation of abusive use and / or drug addiction. The field research was conducted in a therapeutic community in the municipality of Itapecerica da Serra São Paulo, Brazil, in an institution for abusive wearers and drug addicts in the city of Grenoble, France. The field research in France took place from our participation in the double degree program signed by PUC-SP and UPMF-Grenoble / France. The starting point for this analysis consisted in a qualitative study using three methods in coordination. They were: participant observation, case study and actionresearch. The instruments used were: group discussion, in-depth interviews and home visits applied to the research. As a result of this process, some empirical categories emerged, such as drug; the relationship with the family and the community; the look of the subjects on Social Work; the relationship between the exclusion and drug addiction, among others. The study revealed that although there is a need for coordination between the different services and approaches in the sphere of drugs care, which prevails in Brazil is a dynamic competitiveness between the various approaches. The survey also showed that within an interdisciplinary dynamic, the intervention of Social Work emerges with relevance, assessed on a perspective that considers the role of the subject in the reintegration process